Structural changes upon membrane insertion of the insecticidal pore-forming toxins produced by Bacillus thuringiensis - Pacheco, Sabino; Gómez, Isabel; Peláez-Aguilar, Angel E.; Verduzco-Rosas, Luis A.; García-Suárez, Rosalina; do Nascimento, Nathaly A.; Rivera-Nájera, Lucero Y.; Cantón, Pablo Emiliano; Soberón, Mario; Bravo, Alejandra (Frontiers in Insect Science, 2023)
Different Bacillus thuringiensis (Bt) strains produce a broad variety of pore-forming toxins (PFTs) that show toxicity against insects and other invertebrates. Some of these insecticidal PFT proteins have been used successfully worldwide to control diverse insect crop pests. There are several studies focused on describing the mechanism of action of these toxins and have helped to improve their performance and to cope with the resistance that different insects have evolved against some of these proteins. However, crucial information that is still missing is the structure of the pore formed by some of these PFTs, such as the three domain Cry proteins, which are the most commercially used Bt toxins in the biological control of insect pests. In recent years, progress has been made on the description of the structural changes that certain Bt insecticidal PFT proteins undergo upon membrane insertion. In this review, we describe the models that have been proposed for the membrane insertion of Cry toxins. We also review the recently published structures of the vegetative insecticidal proteins (Vip3) and the insecticidal toxin complex (Tc) in the membrane inserted state. Although different Bt PFTs show different primary sequences, there are some similarities in the three-dimensional structures of Vip and Cry proteins. Also, all PFT described here must undergo major structural rearrangements to pass from a soluble form to a membrane inserted state. It is proposed that despite their structural differences, all of them undergo major structural rearrangements producing an extended alpha-helix that plays a fundamental role in perforating their target membrane, resulting in the formation of the membrane pore required for their insecticidal activity.